Developing Student’s Poetry Writing Competence Using the Genius Learning Method in Students’ Literacy Stylistic in Sinar Husni Senior High School - Rosadi, Devi Methia; Sutikno (PT Inovasi Pratama Internasional, 2025)
The problems in this research are as follows: 1) What is the poetry-writing ability of class X students at Sinar Husni Private High School before the genius learning method in stylistics is applied? 2) What is the poetry-writing ability of class X students at Sinar Husni Private High School after applying the genius learning method in stylistics? 3) Is the genius learning method effective in improving the poetry-writing ability of class X students at Sinar Husni Private High School? The objectives of this research are: 1) to determine the poetry-writing ability of the class and 2) to determine the poetry-writing ability of the class academic year 2024-2025. An experimental method is used in this study. The instrument used to collect data is a test in the form of a test essay. The test was used to determine students’ post-writing abilities. To determine the average student score, the data processing technique that the author uses is the average formula (mean), determines the standard deviation, and then determine the final score. The results of the research show that the ability to write poetry in class X of Sinar Husni Private High School for the 2024 academic year -2025 using the genius learning method in literary stylistics, is better than using conventional methods. Thus, the genius learning method in literary stylistics can improve the ability of class X students of Sinar Husni Private High School for the 2024-2025 academic year. This is proven by the value of